Money Predicted Spain as Football World Champion - Jürgen Gerhards; Gert G. Wagner (Weekly Report, 2010)
Historically, football experts' predictions were the only method of predicting the outcomes of championships. Former players, coaches, and nearly all fans have tried their hand at it. And most of these predictions were wrong, since subjective desires and prevailing public opinions always played a major role. In the meantime, however, reliable methods are being used to make scientific predictions. And the methods utilized are becoming more and more complex.
Keywords: B41; Z19; 330; forecasting; forecasting methods; efficiency; FIFA World Cup 2010